2013
DOI: 10.1111/mec.12298
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular‐ and pollen‐based vegetation analysis in lake sediments from central Scandinavia

Abstract: Plant and animal biodiversity can be studied by obtaining DNA directly from the environment. This new approach in combination with the use of generic barcoding primers (metabarcoding) has been suggested as complementary or alternative to traditional biodiversity monitoring in ancient soil sediments. However, the extent to which metabarcoding truly reflects plant composition remains unclear, as does its power to identify species with no pollen or macrofossil evidence. Here, we compared pollen-based and metabarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
132
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(142 citation statements)
references
References 56 publications
(137 reference statements)
8
132
0
Order By: Relevance
“…There are several reasons why the DNA and the traditional palaeoecological approaches produce different results and these have been recently discussed by Parducci et al [7]. One reason may be that the pollen, macrofossil and DNA originate from different plant tissues with only partial mixing and may even represent different plant communities depending on the study environment that is under investigation (lakes or peat).…”
Section: (D) Proxy Biases and Differencesmentioning
confidence: 98%
See 1 more Smart Citation
“…There are several reasons why the DNA and the traditional palaeoecological approaches produce different results and these have been recently discussed by Parducci et al [7]. One reason may be that the pollen, macrofossil and DNA originate from different plant tissues with only partial mixing and may even represent different plant communities depending on the study environment that is under investigation (lakes or peat).…”
Section: (D) Proxy Biases and Differencesmentioning
confidence: 98%
“…These records have indicated that plants have expanded and contracted their ranges many times during the last glacial-interglacial cycles in both hemispheres. A weakness of the fossil pollen record is, however, that the absence of pollen in a sediment sample does not rule out the possibility of small low-density populations [6,7]. In these cases, plant macrofossils, such as bark, leaves and needles, offer stronger evidence of the local presence of taxa, thus complementing pollen analysis [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…A significant amount of pollen is likely present in the samples taken, together with plant fragments and anything else present in the sediment. Parducci et al (2013) showed that sedaDNA metabarcoding is better at detecting plants that produce restricted amounts of pollen, taxa that are difficult to identify with palynology, and rare plants. It is not certain whether the result is from pollen, or DNA from other parts of plants taken from the sediment sample.…”
Section: Ancient Pollen Dna Barcodingmentioning
confidence: 99%
“…Most ancient DNA barcoding studies have used sedimentary ancient DNA (sedaDNA) to provide complementary data to macrofossil identification and classic palynology (Jørgensen et al 2012a;Parducci et al 2013;Pedersen et al 2013). A significant amount of pollen is likely present in the samples taken, together with plant fragments and anything else present in the sediment.…”
Section: Ancient Pollen Dna Barcodingmentioning
confidence: 99%
“…Sedimentary DNA can be used to characterise recent and past biodiversity and thus is suitable to reveal information about past environmental change (Jørgensen et al 2012;Parducci et al 2012;Pedersen et al 2013). A metabarcoding approach to environmental DNA and subsequent DNA sequencing is commonly applied to characterise the composition of communities in environmental samples (Taberlet et al 2012a;Pedersen et al 2015).…”
Section: Introductionmentioning
confidence: 99%